2017
DOI: 10.1111/pace.13055
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Conversion during Dofetilide Treatment for Persistent Atrial Fibrillation

Abstract: Dofetilide is a well-tolerated antiarrhythmic drug with a low incidence of proarrhythmia and an especially high rate of pharmacologic conversion in patients with persistent AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Again, the study results confirmed the hypothesis that implementation of the institution-specific dofetilide initiation protocol would not increase the frequency of dofetilide dose reduction or other adverse events related to the potential for a condensed dosing interval, as there were no statistically significant differences in the frequency of dofetilide dose reduction, TdP, or other adverse events resulting in treatment failure pre- versus post-protocol implementation. Additionally, the frequency of TdP and dofetilide treatment failure identified in this review is consistent with what has been previously reported in the literature [915]. These results alleviate potential concern that the cost savings associated with a reduced duration of hospitalization for dofetilide initiation through utilization of a condensed dosing interval would be realized at the expense of an increase in the frequency of QT prolongation, TdP, or other adverse events resulting in discontinuation of therapy.…”
Section: Discussionsupporting
confidence: 88%
“…Again, the study results confirmed the hypothesis that implementation of the institution-specific dofetilide initiation protocol would not increase the frequency of dofetilide dose reduction or other adverse events related to the potential for a condensed dosing interval, as there were no statistically significant differences in the frequency of dofetilide dose reduction, TdP, or other adverse events resulting in treatment failure pre- versus post-protocol implementation. Additionally, the frequency of TdP and dofetilide treatment failure identified in this review is consistent with what has been previously reported in the literature [915]. These results alleviate potential concern that the cost savings associated with a reduced duration of hospitalization for dofetilide initiation through utilization of a condensed dosing interval would be realized at the expense of an increase in the frequency of QT prolongation, TdP, or other adverse events resulting in discontinuation of therapy.…”
Section: Discussionsupporting
confidence: 88%
“…There was no difference in pharmacologic conversion rates between men and women and no difference in excessive QT prolongation, though all episodes of torsades de pointes occurred in women. They found a dose-response that predicted pharmacologic conversion, where the rate of conversion based on the final dofetilide dosing was 75% for 500 mcg dosing, compared to 9% for 250 mcg dosing and 0% for 125 mcg dosing [ 35 ].…”
Section: Management: Rate Control and Rhythm Controlmentioning
confidence: 99%